Dermatological manifestations during COVID-19 infection: a case series and discussion on the problem of differential diagnosis. - Ridolo, Erminia; Pucciarini, Francesco; Barone, Alessandro; Nouvenne, Antonio; Meschi, Tiziana; Peveri, Silvia; Incorvaia, Cristoforo (Acta Biomedica Atenei Parmensis, 2021)
On March 11, 2019 the World Health Organization (WHO) declared Coronavirus disease-2019 (COVID-19), caused by SARS-CoV-2, as a pandemic. As of 15/01/2021, more than ninety million cases of infections have been confirmed, with almost two million related deaths.SARS-CoV-2 causes bilateral interstitial pneumonia, which can responsible of respiratory failure in the most severe cases, but the virus has also a wide range of other manifestations, including gastrointestinal, cardiovascular, neurological, and cutaneous signs and symptoms. Cutaneous manifestations are an important matter of study for allergy specialists, as they can be specific signs of the infection, but also manifestations of adverse reactions to the medical therapy in use.In this case series, we report four different cases of dermatological manifestations in COVID patients, two in hospitalised patients and two in patients with mild disease, treated at home. The first case reported is a woman, who develops urticaria while being treated at home with mild COVID-infection; the second and the third one case reported are drug- hypersensivity reaction to remdesevir and low molecular weight heparin. The last case reported is a man with mild covid with vasculitic sacral lesions.Key words: COVID pandemic, SARS-CoV-2, dermatological manifestation in covid infections, remdesevir hypersensitivity, covid and urticaria, covid and vasculitic lesions.